2020
DOI: 10.48550/arxiv.2007.15783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suppression of Three-Body Loss Near a p-Wave Resonance Due to Quasi-1D Confinement

Andrew S. Marcum,
Francisco R. Fonta,
Arif Mawardi Ismail
et al.

Abstract: We investigate the three-body recombination rate of a Fermi gas of 6 Li atoms confined in quasi-1D near a p-wave Feshbach resonance. We confirm that the quasi-1D loss rate constant K3 follows the predicted threshold scaling law that K3 is energy independent on resonance, and find consistency with the scaling law K3 ∝ (k a1D) 6 far from resonance [Mehta et al. Phys. Rev. A 76, 022711 (2007)]. Further we develop a theory based on Breit-Wigner analysis that describes the loss feature for intermediate fields. Las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Strong p-wave interactions are rare in nature, so their extreme tunability in ultracold systems [1,2] is an opportunity for discovery [3][4][5]. Despite recent advances in understanding, such as universal relations for p-wave systems [6][7][8][9][10], open questions remain, including the effect of confinement on Feshbach dimers [11][12][13][14][15][16][17][18][19][20][21][22][23] and correlation strength [24][25][26]. One-dimensional systems hold the prospect for duality between strongly interacting odd waves and weakly interacting even waves [27][28][29][30], for a topological phase transition in two-dimensional systems [31,32], and for engineered states [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong p-wave interactions are rare in nature, so their extreme tunability in ultracold systems [1,2] is an opportunity for discovery [3][4][5]. Despite recent advances in understanding, such as universal relations for p-wave systems [6][7][8][9][10], open questions remain, including the effect of confinement on Feshbach dimers [11][12][13][14][15][16][17][18][19][20][21][22][23] and correlation strength [24][25][26]. One-dimensional systems hold the prospect for duality between strongly interacting odd waves and weakly interacting even waves [27][28][29][30], for a topological phase transition in two-dimensional systems [31,32], and for engineered states [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental work on ultracold p-wave alkali systems has focused on the fermionic isotopes 40 K [1,40,41] and 6 Li [2,20,[42][43][44][45], in part because s-wave collisions are easily suppressed with spin polarization. Experimental investigations have included studies of elastic and inelastic [20,42,45,46] collision rates, spectroscopy [8,41,44], and low-dimensional confinement [18,22,23,40].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it has recently been suggested that such atom loss processes may be suppressed in the low-dimensional systems [35][36][37][38] . Shortly afterwards, the corresponding atomic loss measurements in one-dimensional (1D) systems near the pwave Feshbach resonance have been performed in several experimental groups 39,40 . In this regard, a 1D spin-1/2 Fermi gas with an interspin p-wave interaction 41,42 is one of the possible targets for realizing a topological Fermi superfluid because its three-body losses are weak compared to the fully spin polarized case, where the Bose-Fermi duality weakens the Pauli blocking effect in coordinate space at low energy scale [43][44][45][46][47][48][49][50][51][52] .…”
Section: Introductionmentioning
confidence: 99%
“…A particular atomic gas system of recent interest is a spin-polarized Fermi gas confined to one spatial dimension (1D) [15][16][17][18][19][20][21][22][23][24]. Since the gas is spin-polarized, the sor even-wave interactions are suppressed, and the leading interactions are p-or odd-wave in character.…”
Section: Introductionmentioning
confidence: 99%